Continuous recognition: A latent variable approach to measuring international sovereignty of self-determination movements. (November 2020) - Huddleston, R Joseph
How do self-determination groups move toward diplomatic recognition? Although recognition is the dominant activity used to understand international sovereignty, it is perhaps the most costly decision states make towards these groups. Third parties have many substantial interactions with aspiring states, building their sovereignty by other important means. I argue that our understanding of international sovereignty can be improved by conceptualizing it as a dynamic, continuous process, reflected in foreign policy decisions short of the legal recognition. I create a Bayesian latent variable model of international sovereignty, using bilateral data on diplomatic exchange, IGO voting, sanctions, military aid, and intervention in separatist conflicts. Complementing prior work on international sovereignty, my measure provides support for important theoretical expectations previously explored using only recognition as a measure of sovereignty. I find that diplomatic recognition, extant violence, separatist victory, and sour third-party–incumbent relations positively impact latent sovereignty of separatists, while concern for precedent negatively impacts it.